Analysis of the Use of Regional Languages in Biology Scientific Terms for Biology Learning in Biology Department Students at Medan State University - Mohonia Sabarito Sitohang; Amkani Angelita Pakpahan; Atika Wulandari; Hughes Bazura; Ulfi Khairani Zain; Wirda Resinta Gultom; Yuntha N Manda; Syairal Fahmy Dalimunte (Program Studi Pendidikan Biologi FKIP Unpatti, 2025)
Language is a crucial tool in scientific communication, particularly in biology, where precise terminology is essential. While Latin scientific names provide standardization, integrating local languages can enhance students' comprehension and engagement. This study examines the impact of using local languages in biological scientific terms among Biology Department students at Medan State University. A qualitative research approach was applied, using online questionnaires and the Guttman scale for data analysis. The results show that 69.93% of students have a positive perception of local language use in biology learning. Most students believe it improves understanding, preserves cultural heritage, and increases motivation. However, challenges arise when local terms do not align with standardized scientific names, leading to misunderstandings. Some students also find it difficult to translate scientific terms into their local language. Despite these challenges, integrating local language fosters cultural appreciation and active learning. A balanced approach combining local and scientific terms is necessary to ensure clarity and accuracy in biology education.